Compliance tracking system for training element of OSHA process safety management - Hanida, Abdul Aziz; Natasya, Azmi (IOP Publisher, 2018)
Studies show that many accidents have happened in process industries such as in chemical plants that have taken many peoples' lives. One of the contributing factors of such accidents happening is because of inadequate training provided to employees in particular operational training. One of the established standards highlighting this issue is the training element of OSHA Process Safety Management 29 CFR1910.119(g). Apparently the demand for effective ways to implement Process Safety Management (PSM) is on the rise. Basically the efficiency of standard implementation programme process mostly depends on the systematic framework, which means that all the requirements must be considered, ensuring continuity and completing the implementation process. This paper presents a system to track the performance of PSM training programme based on compliance percentage. Furthermore, the system helps process industries to manage and track information, documentations and required actions regarding the PSM training programme in systematic manner. Besides, it also provides a basis for gap analysis to be carried out for programme improvement. Implementation of this system could serve as a lagging indicator for improvement and to ensure the desired competency of plant personnel.